2021
DOI: 10.1002/1878-0261.13085
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific effects of transcription factor TCFL5 on the pluripotency‐related genes SOX2 and KLF4 in colorectal cancer development

Abstract: Colorectal cancer (CRC) is a very common life‐threatening malignancy. Transcription factor‐like 5 (TCFL5) has been suggested to be involved in CRC. Here, we describe the expression of four alternative transcripts of TCFL5 and their relevance in CRC. Complete deletion of all isoforms drastically decreased pro‐tumoural properties such as spheroids formation and in vivo tumour growth, although increased migration in CRC cell lines. Overexpression of the two main isoforms, TCFL5_E8 and CHA, had opposite effects: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Interestingly, germ cell maintenance gen Sox2 54 , Dmrt1 and Dalz are increased in TCFL5 knockout mice. In this regard, we observed that TCFL5 negatively regulates SOX2 in human tumor cells 55 . Thus, it is possible that the constant expression of Sox2 blocks meiosis activating germ cell maintenance signals.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, germ cell maintenance gen Sox2 54 , Dmrt1 and Dalz are increased in TCFL5 knockout mice. In this regard, we observed that TCFL5 negatively regulates SOX2 in human tumor cells 55 . Thus, it is possible that the constant expression of Sox2 blocks meiosis activating germ cell maintenance signals.…”
Section: Discussionmentioning
confidence: 74%